State Estimation of Direct Field Orientation Control Induction Motor Drive by Using Kalman Filter - Mohammed Khalil Hussain (Engineering and Technology Journal, 2012)
Field oriented control (FOC) method of an induction motor (IM), allows high performance speed and torque response to be achieved from an induction motor. The present work selects the direct field orientation control induction motor (DFOCIM) as an effective method for eliminating the coupling effect between torque and flux. In the present work, two schemes of estimators have been used, standard kalman filter (SKF) and Extended kalman filter (EKF) for estimating stator current, rotor flux and rotor speed. The performance comparison is based on evaluation of estimation error of both estimators. The performances of suggested estimators are assessed in terms of tracking performance and noise rejection capability.